Degradation of sulfamethoxazole by chlorination in water distribution systems: Kinetics, toxicity, and antibiotic resistance genes. (16th December 2022) - Xu, Luo; Li, Cong; Wei, Guozijian; Ji, Jie; Lichtfouse, Eric; García, Andreina; Zhang, Yunshu
Abstract: Sulfamethoxazole (SMX) is one of veterinary drugs and food additives, which has been frequently detected in surface waters in recent years and will cause damage to organisms. Therefore, SMX was selected as a target to be investigated, including the degradation kinetics, evolution of toxicity, and antibiotic resistance genes (ARGs) of SMX during chlorination in batch reactors and water distribution systems (WDS), to determine the optimal factors for removing SMX. In the range of investigated pH (6.3–9.0), the SMX degradation had the fastest rate at close to neutral pH. The chlorination of SMX was affected by the initial total free chlorine concentration, and the degradation of SMX was consistent with second‐order kinetics. The rate constants in batch reactors are (2.23 ± 0.07) × 10 2  M −1  s −1 and (5.04 ± 0.30) × 10 M −1  s −1 for HClO and ClO −1, respectively. Moreover, the rate constants in WDS are (1.76 ± 0.07) × 10 2  M −1  s −1 and (4.06 ± 0.62) × 10 M −1  s −1, respectively. The degradation rate of SMX was also affected by pipe material, and the rate followed the following order: stainless‐steel pipe (SS) > ductile iron pipe (DI) > polyethylene pipe (PE). The degradation rate of SMX in the DI increased with increasing flow rate, but the increase was limited. In addition, SMX could increase the toxicity of water initially, yet the toxicity reduced to the level of tap water after 2‐h chlorination. And the relative abundance of ARGs ( sul 1 and sul 2) of tap water samples was significantly increased under different chlorination conditions. Practitioner Points: The degradation rate of SMX in batch reactor and WDS is different, and they could be described by first‐ or second‐order kinetics. The degradation of SMX had the fastest rate at neutral pH. The degradation rate of SMX was also affected by pipe material and flow velocity. SMX increased the toxicity of water initially, yet the toxicity reduced after a 2‐h chlorination. SMX increased the relative abundance of antibiotic resistance genes sul1 and sul2 . Abstract : This paper investigated the kinetics, evolution of toxicity and antibiotic resistance genes (ARGs) of SMX in reactions with free chlorine (FC) to evaluate the fate of SMX in batch reactors and water distribution systems (WDS).